Characteristics of Dry Starters of Indigenous Cocoa Aceh Bacteria Isolate - Yusya Abubakar; Murna Muzaifa; Heru Prono Widayat; Martunis Martunis; Agustia Maulina (Gontor AGROTECH Science Journal, 2019)
This research aims to study dry starter manufacture of isolates Lactic acid bacteria (LAB), Acetic acid bacteria (BAA) and mixture of LAB and AAB isolates for Aceh cocoa fermentation. This research is an exploratory laboratory with 3 stages: the rejuvenation of bacteria, bacterial isolates characterization and manufacture of dry starter. The analysis carried out by analysis of moisture content, cell viability and descriptive organoleptics (flavor, color and texture).The results reveal that the five of isolates BAL and BAAL. sake, L. carnis, L. coryniformis, Gluconobacter sp dan Acetobacter sp) can be rejuvenated well. L. coryniformis and Gluconobacter sp is selected bacteria (potential) that has the ability to degrade protein and pectin. The resulting dried starter had an average water content 9.77% and cell viability 1,3 x 105CFU/g. Organoleptic characteristics of dried starter as a whole has a sour flavor, bright color and smooth texture. The best treatment was obtained by the treatment using selected LAB isolate (L. coryniformis) with the highest cell viability was 1,9 x 107 CFU/g.